2016
DOI: 10.4187/respcare.04295
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Prolonged Mechanical Ventilation in Intensive Care Units in Mainland China

Abstract: INTRODUCTION:In mainland China, there are no special care centers (long-term acute care, weaning, chronic care facilities) for patients requiring prolonged mechanical ventilation (PMV). Our goal was to characterize the prevalence and outcome of patients undergoing PMV in Chinese intensive care units (ICUs). METHODS: A prospective 1-d prevalence study was performed at 55 ICUs, with 28-d follow-up. RESULTS: On the observation day, 622 adult patients occupied ICU beds. Enrollment criteria were met by 302 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
3
15
1
Order By: Relevance
“…In addition, previous studies have shown that PMV patients had a longer duration of MV, ICU stay, and hospital stay compared with those who did not. According to these studies, duration of MV among PMV patients was 29-51 days, ICU stay was 33-52 days, and hospital stay was 51-77 days [2,4,[12][13][14]20]. These studies were conducted in countries lacking the concept of weaning centers, and the results were consistent with those observed in our study.…”
Section: Relationship With Previous Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, previous studies have shown that PMV patients had a longer duration of MV, ICU stay, and hospital stay compared with those who did not. According to these studies, duration of MV among PMV patients was 29-51 days, ICU stay was 33-52 days, and hospital stay was 51-77 days [2,4,[12][13][14]20]. These studies were conducted in countries lacking the concept of weaning centers, and the results were consistent with those observed in our study.…”
Section: Relationship With Previous Studiessupporting
confidence: 89%
“…Conversely, in countries such as Japan lacking weaning centers, patients who require PMV may occupy ICU beds in acute care hospitals for an extended period, thereby affecting the fair allocation of critical care resources [2,4,[12][13][14]. Furthermore, these patients place substantial loads on intensivists throughout the long period of the weaning trial.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects in our weaning-failure group were older than those in the weaning-success group (82.5 years ± 10.3 years versus 70.6 years ± 15.3 years, P = .034). Some studies [ 30 , 31 ] have reported that advanced age is a risk factor for weaning failure. Comorbidities are common in the elderly and a lower comorbidity burden is more likely to result in successful weaning from mechanical ventilation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to evaluate what happens to these patients needing PMV where there is no LWU. A prospective prevalence study [ 70 ] in 55 chinese ICUs, with 28 days follow up, reported that 36.1% of patients had received MV for more than 21 days, 23% of them being weaned. Despite the public health burden required by patients requiring PMV, a systematic review [ 71 ] reports that only 14 articles in the biomedical literature have tested patient-level factors associated with long-term mortality.…”
Section: Main Textmentioning
confidence: 99%